Structure and function of novel antifreeze peptides derived from Glaciozyma antarctica antifreeze protein-1 - Said Amin Shah, Syed Hussinien Hielmie Shah (2013)
Organisms living in cold environment produce antifreeze proteins (AFPs) which exhibit special functions as a result of cold adaptation. AFP is currently being identified in many organisms such as bacteria, plants, fish, and fungi that are exposed to freezing stress. This study aimed to create novel antifreeze peptides based on the three-dimensional structure of Glaciozyma antarctica antifreeze protein-1 (AFP-1). Computational prediction on the structure of AFP-1 suggests that the helical segments of this protein are responsible for antifreeze activity. Six peptides derived from the sequence of G. antarctica have been synthesized. The peptides show measurable antifreeze activity as quantitatively measured by thermal hysteresis (TH) assay and qualitatively by ice recrystallization inhibition (IRI) assay. Structure determination of antifreeze peptides was carried out based on spectroscopic data obtained by using one dimensional and two dimensional 1H-NMR (800 MHz) in elucidating the structures of obtained peptides. All antifreeze peptides showed increase of thermal hysteresis value which is relative to the increase of antifreeze peptides concentration until the saturation point of solution. Peptide 1m recored the highest antifreeze activity with TH value 0.097 ± 0.004 oC, almost similar to the parent protein AFP-1 (0.1oC in concentration 0.1mM). Analysis of relationship between the peptide NMR structure and its activity showed that the peptides form alpha helical structure and the extent of peptide helicity greatly influences the activity of antifreeze peptides derived from G. antarctica AFP-1 segments.